2020
DOI: 10.1159/000506471
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization Treatment for Vulvar Cancer: A Case Report

Abstract: Vulvar cancer is a rare malignant tumor occurring in elderly postmenopausal women. At present, surgery is the main treatment for vulvar cancer. Chemotherapy alone has no obvious therapeutic effect as a treatment for vulvar cancer, so it is often combined with radiotherapy or surgery. Selective arterial infusion chemotherapy and embolization is rarely used for the treatment of vulvar cancer. A 63-year-old Tibetan woman underwent superselective arteriography and embolization. On the 7th day after the operation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Compared to other pelvic malignancies, data for the use of embolization in the management of vulvar cancers are limited. A case study from 2020 used selective arteriography and embolization in a patient with vulvar SCC and found that this technique led to ischemia and spontaneous separation of the exophytic mass from the surrounding labia, thus decreasing the need for a more morbid intervention ( Zhao and Xue, 2020 ). However, there is a paucity of data to guide the use of this modality in the treatment of vulvar masses, and the literature is even more scarce when it comes to its potential utility in the care of patients with vulvar sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other pelvic malignancies, data for the use of embolization in the management of vulvar cancers are limited. A case study from 2020 used selective arteriography and embolization in a patient with vulvar SCC and found that this technique led to ischemia and spontaneous separation of the exophytic mass from the surrounding labia, thus decreasing the need for a more morbid intervention ( Zhao and Xue, 2020 ). However, there is a paucity of data to guide the use of this modality in the treatment of vulvar masses, and the literature is even more scarce when it comes to its potential utility in the care of patients with vulvar sarcomas.…”
Section: Discussionmentioning
confidence: 99%